ARI updates 2013: moving beyond numbers / Accounting Research Institute (Accounting Research Institute (ARI), 2013)
One of the most important expectations of the Higher Institutions' Centre of Excellence ( HICoE ) initiative is the creation of a home-grown global, niche reference centre.